Simultaneous EEG-fMRI : novel methods for EEG artefacts reduction at source - Chowdhury, Muhammad Enamul Hoque (2014)
This thesis describes the development and application of novel techniques to reduce the EEG artefacts at source during the simultaneous acquisition of EEG and fMRI data. The work described in this thesis was carried out by the author in the Sir Peter Mansfield Magnetic Resonance Centre, School of Physics & Astronomy at the University of Nottingham, between October 2010 and January 2013.